An Average Power-Based Planning Framework of Transmission Expansion: A New Role for Energy Storage - Qian Zhang; P. R. Kumar; Le Xie (IEEE Open Access Journal of Power and Energy)
This paper introduces a framework and computational algorithm that utilizes energy storage systems in pairs to improve transmission capacity in electric power systems. Recognizing prolonged development timelines and urgent needs for inter-regional transmission corridors, this paper proposes a near-term supplementary solution that schedules pairs of energy storage systems to increase the throughput of congested transmission lines effectively. We establish a theoretical lower bound on the minimum capacity required for electric power delivery, defined as a function of cumulative power over time. In sharp contrast with conventional transmission planning based on peak power delivery, this new framework allows transmission capacity to be designed around average power delivery needs. This shift would significantly enhance asset utilization in a future grid with large renewable power fluctuations. Numerical experiments demonstrate the proposed method across various grids. In the RTS-GMLC system, the minimum line capacity required was reduced by 36.8% compared to peak-based planning and further decreased by 43.5% when contingency scenarios were considered. In the Texas synthetic grid, the approach achieved a 46.2% reduction in line capacity while maintaining system reliability. These results highlight storage’s potential as a transmission asset, providing practical guidance for planning and policy while enabling insights into future market designs.